ON THE CONVEXITY OF THE JOINT ESSENTIAL NUMERICAL RANGES - CYPRIAN, O. S.; MASIBAYI, ANDREW; OKELO, N. B. (IJRDO -JOURNAL OF MATHEMATICS, 2015)
The concept of essential numerical range of an operator was defined and studied by Stampfli and Williams in 1972. In this paper, we consider the joint essential numerical range of an mtuple of operators T = (